Beyond the Ice: Value Chains and Strengthening the Competitiveness of Ambon Frozen Fish - Ariviana L. Kakerissa (ARIKA, 2025)
The frozen fish industry in Ambon Island plays a vital role in sustaining coastal economies while integrating into Indonesia’s global seafood trade network. This study examines the structure and governance of the frozen fish value chain to understand value distribution, institutional roles, and competitiveness challenges faced by local industries. Data were collected through field observations, stakeholder interviews, and value chain mapping. The findings reveal that buyers and exporters in Surabaya hold dominant control over pricing and quality standards, while fishermen and local processors remain in weak bargaining positions due to limited capital and logistics infrastructure. The regional government, through the Regional Inflation Control Team (TPID), acts as a balancing mechanism between export demands and domestic supply, although its effectiveness is constrained by institutional coordination. Two major structural issues were identified: high logistics costs and dependence on a single buyer. To enhance competitiveness, an integrated strategy is required, combining supply chain efficiency, market diversification, cold-chain infrastructure strengthening, and the adoption of traceability and digital value chain systems to support the development of geographical branding for Ambon’s fishery products. The study highlights the necessity of a structural shift toward a value-based, sustainable, and inclusive fisheries economy.